Influence of thermochemical sulfate reduction on oxygen isotopic composition of calcite cements in carbonates of the Triassic Feixianguan and Permian Changxing formations in the Sichuan Basin, China - Wang, Guangwei; Hao, Fang; Zou, Huayao; Li, Pingping (Frontiers in Earth Science, 2023)
Calcite cement is a common diagenetic mineral in carbonate rocks and plays an important role on rock quality as hydrocarbon reservoirs. Traditionally, oxygen isotopic compositions (δ18O) of the diagenetic calcites tend to decrease with increasing depths due to temperature-dependent isotope fractionation. In this study, the stable isotope compositions of the calcite cements in the Changxing and Feixianguan formations from the Puguang, Yuanba, Jiannan and Fuling carbonate fields in the Sichuan Basin were analyzed. The results show that some calcite cements have δ18O values similar to those of their host carbonates, despite the fact that these calcites formed at elevated temperatures (> ~100oC). Based on petrographic and geochemical analyses, the 18O-enriched calcites commonly occur with solid bitumens and have lower δ13C values compared with host rocks, suggesting thermochemical sulfate reduction (TSR) provided organic carbon for these calcite precipitation. During TSR, thermal oxidation of hydrocarbons generated the light carbon, and simultaneously the reduced sulfate ions provided the oxygen. Comparison of our study with the TSR calcites worldwide, a model for oxygen isotope behavior during TSR was established. Oxygen isotope compositions of TSR-related calcites are a function of isotope compositions and amounts of the initial anhydrite and pore waters. TSR shows two opposing effects on the δ18O values of calcites, depending on the δ18O ratios of the initial anhydrite. The reduction of anhydrite with relatively low δ18O values causes the calcite δ18O lower than theoretical values of calcites directly precipitated from pore waters. The heavy δ18O ratios of calcites formed during TSR are not only attributed to the 18O-enriched pore water resulting from extensive water-rock interaction, but also probably due to the involvement of anhydrite with high δ18O values.